2000
DOI: 10.1002/j.2161-1874.2000.tb00142.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adolescent Sex Offender Abuse History on Counselor Attitudes

Abstract: Counseling students' judgments of adolescent sex offenders with sexual or physical abuse histories were examined. Sexually abused offenders were more desirable as prospective clients than were nonabused offenders. Sexually abused counselors desired to see physically abused offenders as clients over sexually abused offenders. Implications for counseling are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 10 publications
0
11
1
Order By: Relevance
“…Carone and LaFleur (2000) conducted an experimental analogue study with 236 counselors-in-training who were enrolled in one of eight counselor education master’s degree programs located in two Mid-Atlantic States. The student counselors were asked to respond to demographic questions and were administered the Counselor Response Form (CRF) to determine the counselors’ judgment of adolescent sexual offender clients.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Carone and LaFleur (2000) conducted an experimental analogue study with 236 counselors-in-training who were enrolled in one of eight counselor education master’s degree programs located in two Mid-Atlantic States. The student counselors were asked to respond to demographic questions and were administered the Counselor Response Form (CRF) to determine the counselors’ judgment of adolescent sexual offender clients.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Public awareness and concern about the problem of sexual violence has increased because of the escalating incidences of sexual crimes (Brown, 1999; Sanghara & Wilson, 2006). The attitude of the general public toward sexual offenders appears to be highly negative (Carone & LaFleur, 2000; Nelson, 2007; Rash & Winton, 2007; Valliant, Furac, & Antonowicz, 1994). A significant number of adult sexual offenders began their criminal offenses during adolescence, and sexual crimes by children against children are contributing to the rising incidence of sexual crimes (Lakey, 1994; Van Outsem, 2002; Van Outsem et al, 2006; Verheij, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from the sexual offending behaviors, JSOs bring a variety of obstacles with them into treatment, such as attitudes and beliefs that challenge both the treatment process and the counselor (Mann & Rollnick, 1996). Even though research concerning the therapeutic treatment of JSOs has been limited (as compared with that of adult sex offenders; Miner, 2002), JSO treatment may be challenging because of (a) the ambivalence that JSOs experience toward counseling, (b) the specific developmental levels and traits of JSOs, and (c) the limited research supporting effective treatment approaches with this client population (Carone & LaFleur, 2000;Mann & Rollnick, 1996). We explore each of these challenges.…”
Section: Potential Challenges Concerning the Treatment Of Jsosmentioning
confidence: 99%
“…Although research concerning the treatment of JSOs has been limited (Andrade et al, 2006;Carone & LaFleur, 2000), Ginsburg et al (2002) found treatment similarities between addictions and sexual offender counseling. For example, both client populations tend to be resistant and challenging, and relapse prevention strategies are normally integrated with both populations.…”
Section: Potential Challenges Concerning the Treatment Of Jsosmentioning
confidence: 99%